Dietary pattern adherence in patients with type II diabetes mellitus - Tiara Fatma Pratiwi; Achmad Wahdi; Novia Susanti; Hakim Tobroni HR; Rickiy Akbaril Okta Firdaus (Jurnal Keperawatan Komprehensif (Comprehensive Nursing Journal), 2021)
Aims : Modern lifestyle with many choices of food menus that contain high glucose results in non-adherence to diet in patients with diabetes mellitus. The purpose of this study was to determine the description of dietary non-compliance in patients with type II diabetes mellitus. Design : This type of research is descriptive research. The population is 50 people at the age of 30-60 with a sample of 46 respondents. Methdos : The independent variable is non-adherence to diet in patients with type II diabetes mellitus. The research instrument used a diet questionnaire and analyzed with descriptive frequency. Results : : The results showed that from 46 respondents, most (63.0%) had a diet with low adherence. Conclusions : Patients with Type II Diabetes Mellitus in RT 02 Wonokromo mostly have a low level of adherence and are expected to add insight and knowledge about dietary adherence in people with diabetes mellitus and further research can be developed based on other factors in the hope of new insights.